(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Individual variation in drug response is a major problem in clinical practice and drug development, which ranges from therapeutic failure to adverse drug reaction as well as drug interaction in multidrug therapy. Pharmacogenetics is relevant in this aspects and mainly concern with the study of genetic variation, which influence individuals responses to drug. Again, polymorphism (variation) in the genes which are involved in encoding drug metabolizing enzymes, transporters of drug and ion channels can play role in the adverse drug reaction in an individual or can interfere with the therapeutic efficacy. By studying pharmacogenetics one can apply genotyping of polymorphic alleles that encodes drug metabolizing enzymes to identify individuals drug metabolism phenotype and correlating this knowledge to dosing or drug selection, avoidance of many adverse effect of drug and therapeutic failure is possible as well as economic burden to the patient will be reduced. It is true that one drug will not effective for everyone and everyone will not response to a single drug in a similar fashion. It is almost impossible to test every drug in whole population in respect of investment and time. From this point of view, pharmacogenetic screening, such as phenotying test can be useful to identify patients who have inherent risk factor for a specific adverse drug reaction. Recently pharmacogenetic testing is performed for only a few drugs e.g. mercaptopurine, thioguanine, azathriopine and tacrine and the facility is also available in a limited number of teaching hospital but the days are not so far, when it may be considered as unethical if pharmacogenetics test is not done routinely before prescribing a drug to a patient. http://dx.doi.org/10.3329/bjpp.v26i1-2.19966 Bangladesh J Physiol Pharmacol 2010; 26(1&2) : 34-42